A Study of Supply Chain Manangement of Board Composition, Enterprise Risk Management, and Performance of non and Islamic Companies in Indonesia - Jumadil Saputra; Husaini Husaini; Saiful Saiful; Wahyuddin Albra (International Journal of Supply Chain Management, 2019)
The purpose of this study is to investigate the differences of firm performance between Islamic and non Islamic companies. Further, this study also examine the influence of the board size, independence board and enterprise risk management (ERM) on firm performance. The sample in this study is non-financial companies listed on the Indonesia Stock Exchange with the period 2011-2015, with a total of 95 Islamic and 858 non-Islamic companies. The results of this study shows that there is significant different the performance of Islamic and non Islamic companies.Â The performance of Islamic companies are higher than non-Islamic companies. Further,Â this study found that board size has no effect on the market performance of those companies. independence board has a negative effect on the market performance of the companies. enterprise risk management positively affects the firm performance for both Islamic and non-Islamic companies.